Design and protocol of the Buprenorphine plus Outpatient Parenteral Antimicrobial Therapy (B-OPAT) study: a randomized clinical trial of integrated outpatient treatment of opioid use disorder and severe, injection-related infections. (July 2022) - Fanucchi, Laura C.; Murphy, Sean M.; Surratt, Hilary; Kapadia, Shashi N.; Walsh, Sharon L.; Grubbs, James A.; Thornton, Alice C.; Nuzzo, Paul; Lofwall, Michelle R.
Introduction: A marked increase in hospitalizations for severe, injection-related infections (SIRI) has been associated with the opioid epidemic. Outpatient parenteral antibiotic therapy (OPAT) is typically not offered to persons with opioid use disorder (OUD) and SIRI, though increasing evidence suggests it may be feasible and safe. This study evaluates the efficacy and cost-effectiveness of an integrated care model combining Buprenorphine treatment of OUD with OPAT for SIRI (B-OPAT) compared with treatment as usual on key OUD, infectious disease, and health economic outcomes. B-OPAT expands and incorporates key elements of established clinical models, including inpatient initiation of buprenorphine for OUD, inpatient infectious disease consultation for SIRI, office-based treatment of OUD, and OPAT, and includes more frequent clinical outpatient visits than standard OPAT. A qualitative evaluation is included to contextualize effectiveness outcomes and identify barriers and facilitators to intervention adoption and implementation. Methods: B-OPAT is a single-site, randomized, parallel-group, superiority trial recruiting 90 adult inpatients hospitalized with OUD and SIRI who require at least 2 weeks of intravenous (IV) antibiotic therapy. After screening, eligible participants are randomized 1:1 to either discharge once medically stable to an integrated outpatient treatment care model combining Buprenorphine and OPAT (B-OPAT) or to Treatment As Usual (TAU). The primary outcome measure is the proportion of urine samples negative for illicit opioids in the 12 weeks after discharge from the hospital. Key secondary OUD outcomes include self-reported number of days of illicit opioid abstinence and 12-week retention in buprenorphine treatment. The infection outcomes are completion of recommended IV antibiotic therapy, peripherally inserted central catheter (PICC) complications, and readmission related to primary SIRI. Conclusions: The B-OPAT study will help address the important question of whether it is clinically effective and cost-effective to discharge persons with OUD and SIRI to an integrated outpatient care model combining OUD treatment with OPAT relative to TAU (Clinicaltrials.gov Identifier: NCT04677114).